Pengaruh Capital Adequacy Ratio, Return on Asset, Loan to Deposit Ratio dan Non Performing Loan Terhadap Laba Bersih pada Bank BUMN yang Terdaftar di Bursa Efek Indonesia Periode 2014 – 2018 - Yunan Surono; Saiyid Syeikh; Ade Rinaldi (J-MAS (Jurnal Manajemen dan Sains), 2020)
This research aims to analyze the effect of simultaneous capital adequacy ratio, return on asset, loan to deposit ratio and non performing loan on the net profit of government public banks in Indonesia Stock Exchange. The effect of partial capital adequacy ratio, return on asset, loan to deposit ratio and non performing loan on the net profit of government public banks in Indonesia Stock Exchange. The research methodology is descriptive and quantitative analysis methods. Data used is secondary data. The population become object in this research is government public bank period of year of 2014-2018. Amount sample the used is the fourth (4)  government public bank and still stand up during period of perception and also publicized of year of 2014-2018 by Indonesian Stock Exchange the analysis multiple regression, hypotesis test so determinant coefficient F test  and  t test. The object of this research is foreign exchange bank listed on the Stock Exchange Indonesia 2014-2018. The sampel in the receach is PT Bank Negara Indonesia,Tbk (BBNI), PT Bank Rakyat Indonesia,Tbk (BBRI), PT Bank Tabungan Negara,Tbk (BBTN), PT Bank Mandiri,Tbk (BMRI), Results of multiple regression equation is Y =  11,469 + 1,30X1  +  1,599X2  - 5,069X3  + 0,481X4  + e,  F test result, it is known that  capital adequacy ratio, return on asset, loan to deposit ratio and non performing loan simultaneously on the net profit. F count larger than F table (52,763 > 3,06) or comparing the significant level of 0.05 then (0.000 < 0.05) then Ho is rejected and Ha accepted. Based on the results of the t test capital adequacy ratio, return on asset and loan to deposit ratio have significant effect between the net profit  (tcount> ttable).Conclusion is the capital adequacy ratio, return on asset, loan to deposit ratio and non performing loan simultaneously on the net profit.. While partially have variable capital adequacy ratio, return on asset and loan to deposit ratio have significant to net profit